Multidimensional Challenges Toward Sustainable Development Tourism in Bali - Wulandari, Ni Putu Paramitha (Bali Tourism Journal, 2024)
Climate change, increasing tourist arrivals, and tourism-related modernization have placed immense strain on the island’s ecosystems. Bali welcomed 5.27 million international tourists. While this influx bolstered the economy, it also exacerbated issues such as carbon emissions, tourism-related waste, and the degradation of natural habitats. In response, the government has initiated bold measures to mitigate environmental damage. One such initiative is Bali Emisi Nol Bersih 2045, which aims to reduce carbon emissions through clean energy transitions and the adoption of environmentally friendly technologies. The introduction of electric vehicles, solar energy projects, and community-led waste management systems represents crucial steps toward sustainability. However, the success of these initiatives hinges on collaboration between stakeholders, including government agencies, local and the tourism industry. In conclusion, addressing climate change in Bali requires a comprehensive and collaborative approach that balances environmental preservation, economic development, and cultural integrity. The implementation of the FOLU Net Sink Program highlights the critical role of forests as carbon sinks. It emphasizes the need for sustainable land-use practices to achieve net-zero emissions. Integrating advanced technologies, such as modern forest management systems and sustainable agriculture, ensures that conservation efforts not only mitigate carbon emissions but also provide economic benefits to local communities. This approach is further strengthened by the Penta Helix model, which fosters synergy among academia, businesses, government, communities, and media to achieve shared environmental goals. Through these efforts, Bali is positioning itself as a global leader in sustainable tourism, demonstrating how innovation and tradition can coexist to address contemporary environmental challenges.